Assessment of the Effects of Dry Spell on the Yield of Maize During the Growing Season in Sokoto State, Nigeria (2010-2019) (Journal of Geography, Meteorology and Environment, 2022)
This work examined the effects of dry spells on the yield of maize in Sokoto State in Nigeria using the daily rainfall data obtained from Nigeria Metrological Agency (NIMET) Abuja for a period of 10 years (2010-2019); used to determine the trends in the dates of onset and cessation of dry spells using MAKESENS while the data on the yield of maize was collected from Agricultural Development Program (ADP) office in Sokoto state for a period of 10 years (2010-2019), used together with the frequency of dry spells to determine the perceived effects of dry spells on the yield of maize. Trends on the occurrence and frequency of dry spell were also determinedfocusing only on the raining months (May to October).LinearRegression analysis and correlation analysis was done to determine the effects of dry spell on maize yield. The results showed that the onset of dry spells ranged from 9th April, in 2015 to 1st June in 2012; showing fluctuations in three months (April, May & June) as well as in date in the months. The cessation dates of dry spells occurred in two months (September & October) but was stable in October, it fluctuated within the month, having the maximum cessation dates to be 25th October and the minimum date to be 22th September. It was concluded that there are changes in the onset and cessation of dry spells of rainfall due to the changes in rainfall characteristics which also affected the variability of the onset and cessation of dry spells. The studyalso shows recent changes in the trends of dry spells from year to year. The perceived effects of dry spells of rainfall showed negativecorrelation with maize yield,implying a significant relationship between dry spells and the yield of maize.
Keywords: Climate Change; Dry spell; Maize yield; Markov Chain and Rainfall